Fault tolerance : a novel - Valdes, Valerie (Harper Voyager, an imprint of HarperCollinsPublishers, 2022)
Cargo ship captain Eva Innocente and her crew on the La Sirena Negra try to figure out why hundreds of monoliths have appeared in space broadcasting the same looped message to surrender or die.